Effect of intercalated cell-specific Rh C glycoprotein deletion on basal and metabolic acidosis-stimulated renal ammonia excretion - Lee, Hyun-Wook (American Physiological Society, 2010)
Rh C glycoprotein (Rhcg) is an NH(3)-specific transporter expressed in both intercalated cells (IC) and principal cells (PC) in the renal collecting duct. Recent studies show that deletion of Rhcg from both intercalated and principal cells inhibits both basal and acidosis-stimulated renal ammonia excretion. The purpose of the current studies was to better understand the specific role of Rhcg expression in intercalated cells in basal and metabolic acidosis-stimulated renal ammonia excretion. We generated mice with intercalated cell-specific Rhcg deletion (IC-Rhcg-KO) using Cre-loxP techniques; control (C) mice were floxed Rhcg but Cre negative. Under basal conditions, IC-Rhcg-KO and C mice excreted urine with similar ammonia content and pH. Mice were then acid loaded by adding HCl to their diet. Ammonia excretion after acid loading increased similarly in IC-Rhcg-KO and C mice during the first 2 days of acid loading but on day 3 was significantly less in IC-Rhcg-KO than in C mice. During the first 2 days of acid loading, urine was significantly more acidic in IC-Rhcg-KO mice than in C mice; there was no difference on day 3. In IC-Rhcg-KO mice, acid loading increased principal cell Rhcg expression in both the cortex and outer medulla as well as expression of another ammonia transporter, Rh glycoprotein B (Rhbg), in principal cells in the outer medulla. We conclude that 1) Rhcg expression in intercalated cells is necessary for the normal renal response to metabolic acidosis; 2) principal cell Rhcg contributes to both basal and acidosis-stimulated ammonia excretion; and 3) adaptations in Rhbg expression occur in response to acid-loading.